PENERAPAN AKAD ISTISHNA’ PADA KPR SYARIAH ASTER VILLAGE CIWASTRA DI PT ROYAL BRIDEA INDONESIA - Nurmala, Risma; Mubarok, Jaih; Hasanudin, Muhammad (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2020)
In the case of house purchases in it will be given the breadth to continue or cancel the contract (khiyar), in the implementation of the Aster Village Ciwastra only allow khiyar majelis while khiyar conditions are not allowed. This study aims to determine the concept of Aster Village Ciwastra sharia mortgages at PT Royal Bridea Indonesia, know the operational system of Aster Village Ciwastra sharia mortgages at PT Royal Bridea Indonesia, and the application of the istishna 'contract that has been applied, is it in accordance with DSN-MUI fatwa No 06 year 2000 about buying and selling istishna'. The method used is descriptive which aims to explain or describe the practice of istishna contract 'at Aster Village Ciwasta. Based on the results of the study, it can be concluded 1). The concept of sharia mortgages used by Aster Village Ciwastra at PT Royal Bridea Indonesia is a concept of ownership that is paid directly to the developer without involving the bank. 2). Sharia KPR operational system used is a 5-year KPRS with a system without a bank, without interest, without confiscation, and without a contract that is false. 3). The application of the istishna contract 'at Aster Village Ciwastra sharia mortgages at PT Royal Bridea Indonesia was reviewed with fatwa No 06 / DSN - MUI / IV / 2000 concerning the sale and purchase of istishna' not yet in full compliance, namely in the case of the provisions of item 5 (mustashni buyers' may not be allowed sell goods before the recipient) and 7 (in case there is a defect or the goods are not in accordance with the agreement, the customer has a khiyar right (the right to vote) to continue or cancel the contract), whereas in the implementation prior to the agreement it has been stipulated that only allows the khiyar of the assembly while the khiyar is a condition not allowed. There are also other matters regarding the provisions of points 2 and 3.